Observations on the Flying Squirrels Petaurista petaurista philippensis (Elliot) and Petinomys fuscocapillus (Jerdon) in Periyar Tiger Reserve and its Neighbourhood - Zacharias, V. J.; Bhardwaj, A. K. (Indian Forester, 1997)
No abstract